Réflexions sur une linguistique de discours comparative: le cas du journal télévisé enFrance et en Allemagne - Münchow, Patricia von (My University, 2004)
This article is a brief summary of the author's work on what she calls comparative discourse linguistics. The long-term aim of comparative discourse linguistics is to compare different discursive cultures through the description and interpretation of the verbal productions characterizing them. The comparison does not primarily concern different languages but the expressions of a series of genres in two or more ethnolinguistic communities. This approach raises a number of theoretical and methodological issues discussed in the first part of the paper, such as the status of genres as tertium comparationis, the nature of analytic categories and the relevance and the reach of interpretation. The second part of the article illustrates the principles discussed in the first part. Taking the genre television news program as an example, the author describes and interprets important differences between French and German programs, focusing in particular on the more or less conventional appearance of the programs, the image of the medium and of the "mediator" and the respective kinds of communities created between journalists and viewers.